MBCL-21. EARLY CHILDHOOD MEDULLOBLASTOMA: SUBGROUP-SPECIFIC SURVIVAL IN PATIENTS TREATED WITH SYSTEMIC CHEMOTHERAPY AND INTRAVENTRICULAR MTX TO AVOID CRANIOSPINAL RADIOTHERAPY. Issue 2 (22nd June 2018) - Mynarek, Martin; Kool, Marcel; Schueller, Ulrich; von Hoff, Katja; Sharma, Tanvi; Rudneva, Vasilisa; Pietsch, Torsten; Northcott, Paul; Juhnke, B -Ole; Meissner, Barbara; Warmuth-Metz, Monica; Kortmann, Rolf D; et al.
Abstract: PURPOSE/METHODS: Methylation-based tumor classification results were obtained from 86 patients younger than four years with medulloblastoma treated with systemic chemotherapy and intraventricular methotrexate to avoid craniospinal radiotherapy (CSI). 70 were HIT trial participants and 16 observational patients. Subgroup specific survival was analyzed. RESULTS: Median follow-up was 8.3 years in the 61 patients alive at last follow-up. 33 patients presented with metastatic disease. Methylation profiling results were WNT (n=1), SHH_INF (n=43), Group 3 (GRP3; n=32) and Group 4 (GRP4; n=10). Of 39 patients with desmoplastic/nodular histology, 38 patients had SHH_INF, one GRP4 medulloblastoma. Survival differed significantly according to methylation subgroup (5y-PFS WNT: 0%, SHH_INF: 79%, GRP3: 31%, GRP4: 70%, p<0.001; 5y-OS: WNT 100%, SHH_INF: 95%, GRP3: 43%, GRP4: 100%, p<0.001). Within the SHH_INF subgroup, no additional risk factors were identified (SHH-I [n=23] vs. SHH-II [n=20; p=0.767(PFS)/0.177(OS)], chromosome 2 gain [n=10; p=0.123(PFS)/0.430(OS)], chromosome 9q loss [n=16; p=0.904(PFS)/0.224(OS)]). In GRP3 medulloblastoma, neither MYC-amplification (n=11, p=0.172[PFS]/0.064[OS]) nor metastatic disease (n=17; p=0.710[PFS]/0.971[OS]) predicted survival. 5-year radiotherapy free survival (CSI or local RT) was WNT: 0%, SHH_INF: 81%, GRP3: 6% and GRP4: 40%; p<0.001. CONCLUSION: In contrast to previously reported poor outcomes in patients with SHH-infant medulloblastoma subgroup SHH-I when treated with systemic chemotherapy alone, chemotherapy with intraventricular methotrexate was effective and avoided CSI in both SHH infant subgroups. The role of intraventricular MTX in this context needs further evaluation. Outcome for GRP3 medulloblastoma was poor, independent of other risk factors. Patients with GRP3 or GRP4 medulloblastoma frequently received radiotherapy for relapsing or non-responsive disease.